Making Waves: To Innovate or Be a Fast Second? - Yung, Chris (Journal of Financial and Quantitative Analysis, 2016)
Abstract Internal finance leads to a stalemate in innovation games; each firm wants to free-ride on the others’ costly experimentation. When instead innovation is financed externally (e.g., with venture capital or initial public offerings), there is an endogenous cost to delay. Waiting to make risky irreversible investment conveys pessimistic information. I characterize the relative sizes of waves of leaders and followers in innovation cycles, and the endogenous, intertemporal distribution of quality as each wave builds and crashes. Finally, old waves leave an adverse selection “hangover,” such that too much early innovation can cause the market for future innovation to break down.